Between Coercion and Compassion: A Comparative Analysis of ‘Amr al-Maʻrūf Nahy ʻan al-Munkar in Qāḍī ʻAbd al-Jabbār’s Rationalism and Abū Ḥāmid al-Gazālī’s Sufi Ethics - Akhmad Jazuli Afandi; Muhyidin Muhyidin (Fikri : Jurnal Kajian Agama, Sosial dan Budaya, 2025)
This article explores the concept of ‘Amr al-Maʻrūf Nahy ʻan al-Munkar (enjoining righteousness and forbidding evil) in Islamic theology through a comparative analysis of two influential thinkers: Qāḍī ʻAbd al-Jabbār (Muʻtazilī rationalist) and Abū Ḥāmid al-Gazālī (Asyʻarī-Sufi scholar). Modern religious violence frequently arises from stringent interpretations of these teachings, highlighting the necessity to examine how classical scholars reconciled ethical imperatives with humanistic principles. The study analyzes primary texts using hermeneutic and comparative methods, including Qāḍī ʻAbd al-Jabbār’s Syarh al-Uṣūl al-Khamsah and Abū Ḥāmid al-Gazālī’s Iḥyā’ ʻUlūm al-Dīn, to illustrate differing approaches. While Qāḍī ʻAbd al-Jabbār focused on rational-legal criteria for intervention, Abū Ḥāmid al-Gazālī emphasized spiritual intention and social harmony. Key findings show (1) the Muʻtazilī prioritization of systemic justice and epistemic clarity versus the Sufi focus on moral self-reformation and gradualism; (2) the role of humanism (e.g., reducing harm, maintaining dignity) across both frameworks despite theological differences; and (3) their relevance to modern debates on religious authority and pluralism. The study concludes that these classical models offer nuanced alternatives to coercive enforcement of ‘Amr al-Maʻrūf Nahy ʻan al-Munkar, promoting a compassion-driven ethics adaptable to diverse socioreligious contexts. Therefore, this article is intended to introduce a novel conceptual framework by bridging Muʻtazilī rationalism and Sufi ethics in understanding the doctrine of ‘Amr al-Maʻrūf Nahy ʻan al-Munkar, integrating rational-legal principles with spiritual compassion to reinterpret this duty beyond a coercive paradigm. Furthermore, underscores the urgent need to safeguard human dignity and the common good within diverse, multicultural societies.